Art management of Batavia Madrigal Singer (BMS) in the International Choir Competition - Putra, Agustinus Arbi; Budiawan, Hery; Safrina, Rien (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2025)
This study aims to find out the management of the Batavia Madrigal Singers (BMS) choir, especially in achieving achievements at the international level. Batavia Madrigal Singers is a choir from Indonesia that is consistent in participating in and winning choir competitions at the international level. This study uses a qualitative research method with a descriptive approach through observation techniques, interviews, and literature studies. The results of the study show that the art management of Batavia Madrigal Singers includes (1) Planning, (2) Organization, (3) Leadership, and (4) Control. Based on the results of the research, it was found that Batavia Madrigal Singers has good management in terms of careful planning, structured organization, quality leaders, and periodic control. In addition to its management, Batavia Madrigal Singers also has members with competent abilities and high commitment from various backgrounds. Batavia Madrigal Singers has carried out its management function well in routine activities and when participating in choir competitions at the international level.